Association of Maternal Exposure to Persistent Organic Pollutants in Early Pregnancy With Fetal Growth - Ouidir, Marion (JAMA Pediatr, 2020)
IMPORTANCE: Prenatal exposure to persistent organic pollutants (POPs) has been associated with birth size, but data on fetal growth and among racially/ethnically diverse pregnant women remain scarce. OBJECTIVES: To assess the association between maternal plasma POPs in early pregnancy and fetal growth and by infant sex and maternal race/ethnicity. DESIGN, SETTING, AND PARTICIPANTS: This cohort study used the National Institute of Child Health and Human Development Fetal Growth Studies–Singleton cohort, which recruited nonobese, low-risk pregnant women before 14 weeks’ gestation between July 1, 2009, and January 31, 2013, in 12 community-based clinics throughout the United States. Participants self-identified their race/ethnicity, self-reported their behavioral risk factors, and were followed up throughout their pregnancy. Data were analyzed from July 31, 2018, to June 3, 2019. EXPOSURES: Levels of 76 POPs in early gestation plasma were measured: 11 perfluoroalkyl and polyfluoroalkyl substances, 1 polybrominated biphenyl, 9 polybrominated diphenyl ethers (PBDEs), 44 polychlorinated biphenyls (PCBs), and 11 organochlorine pesticides (OCPs). The bayesian kernel machine regression method was used to examine chemical class mixtures, and generalized additive mixed model was used to analyze individual chemicals. MAIN OUTCOMES AND MEASURES: Fourteen fetal biometrics were measured, including head circumference, abdominal circumference, and femur length, within 5 ultrasonography appointments. RESULTS: A total of 2284 low-risk pregnant women were included: 606 women (26.5%) self-identified as white with a mean (SD) age of 30.3 (4.4) years, 589 (25.8%) as black with a mean (SD) age of 25.5 (5.5) years, 635 (27.8%) as Hispanic with a mean (SD) age of 27.1 (5.5) years, and 454 (19.9%) as Asian with a mean (SD) age of 30.5 (4.5) years. A comparison between the 75th and 25th percentile of exposure revealed that the OCP mixture was negatively associated with most fetal growth measures, with a reduction of 4.7 mm (95% CI, −6.7 to −2.8 mm) in head circumference, 3.5 mm (95% CI, −4.7 to −2.2 mm) in abdominal circumference, and 0.6 mm (95% CI, −1.1 to −0.2 mm) in femur length. Higher exposure to the PBDE mixture was associated with reduced abdominal circumference (–2.4 mm; 95% CI, −4.0 to −0.5 mm) and femur length (−0.5 mm; 95% CI, −1.0 to −0.1 mm), and the dioxin-like PCB mixture was associated with reduced head circumference (–6.4 mm; 95% CI, −8.4 to −4.3 mm) and abdominal circumference (–2.4 mm; 95% CI, −3.9 to −0.8 mm). Associations with individual chemicals were less consistent. There were some interactions by fetal sex, although most of the results did not vary by maternal race/ethnicity. For example, oxychlordane (–0.98 mm; 95% CI, –1.60 to –0.36 mm; P for interaction <.001), trans-nonachlor (–0.31 mm; 95% CI, –0.54 to –0.08 mm; P for interaction = .005), and p,p’-dichlorodiphenyldichloroethylene (–0.19 mm; 95% CI, –0.22 to –0.09 mm; P for interaction = .006) were associated with shorter femur length among boys only. CONCLUSIONS AND RELEVANCE: This study found that, among pregnant women with low POP levels, a mixture of OCPs was negatively associated with most fetal growth measures and that mixtures of PBDEs and dioxin-like PCBs were associated with reduced abdominal circumference. These findings suggested that, although exposures may be low, associations with fetal growth are apparent.